Association of left ventricular structural remodeling types with fibronectin deficiency in patients with multivessel coronary artery disease - A. R. Mingalimova; N. G. Gumanova; N. M. Bikbova; O. N. Dzhioeva; M. S. Pokrovskaya; I. A. Efimova; Z. Z. Serebryanskaya; N. L. Bogdanova; A. L. Borisova; O. M. Drapkina (Российский кардиологический журнал)
Aim. To evaluate the serum fibronectin level in patients with multivessel coronary artery disease, and to identify the relationship of fibronectin level with atrial fibrillation (AF) developed in the hospital after coronary artery bypass grafting (CABG) and types of left ventricular (LV) structural remodeling.Material and methods. This prospective observational study of 80 patients after elective CABG at the Cardiac Surgery Department № 1 of the N. V. Sklifosovsky Research Institute for Emergency Medicine from October 2020 to May 2022. The groups were divided depending on the development of AF after CABG surgery (19 patients with AF developed in the hospital after CABG (up to 10 days), 61 patients — control group). All patients underwent a general clinical examination and transthoracic echocardiography, with estimation of left ventricular remodeling type. Serum fibronectin level was determined by enzyme immunoassay using the Fibronectin agent (Technozym, Austria).Results. The median fibronectin values in the group with AF was 110,10 [86,86; 134,00] mcg/ml versus 120,90 [92,01; 161,50] µg/ml of the comparison group (p=0,19). The following LV patterns were observed: normal LV geometry (NLVG) — in 1 patient (5,26%), concentric LV remodeling (CLVR) — in 3 patients (15,79%), concentric LV hypertrophy (CLVH) — in 10 patients (52,63%), eccentric LV hypertrophy (ELVH) — in 5 patients (26,32%). In the group without AF, 25 patients (40,98%) were diagnosed with NLVG, 26 patients (42,62%) — CLVR, 6,56% (n=4) — CLVR, while ELVH was diagnosed in 6 patients (9,84%). Differences in geometry types between groups were significant (p<0,0001). Multivariate analysis adjusted for gender, age, cardiopulmonary bypass time, the predictive value remained for CLVH — odds ratio 15,83 (95% confidence interval, 4,0821,442,00; p=0,0001) and ELVH — odds ratio 5,17 (95% confidence interval, 1,36519,573; p=0,015). A further study showed that fibronectin <116,496 µg/ml with a sensitivity of 78% and specificity of 53% is associated with CLVH (p=0,006) in patients of both groups.Conclusion. Fibronectin <116,496 µg/ml is associated with CLVH in patients with multivessel coronary artery disease (sensitivity 78%, specificity 53%; p=0,006).